Ergonomic port placement in robotic colorectal surgery. (27th July 2021) - Wong, Shing Wai; Ang, Zhen Hao; Chua, Jia Lin; Crowe, Philip
Abstract: Aim: The aim of the study was to determine how spacing between ports and alignment of ports (oblique or vertical) influences manipulation angles in robotic colorectal surgery. Method: Abdominal CT scans of 10 consecutive robotic right hemicolectomy and 10 consecutive robotic high anterior resection patients were analysed. The manipulation angles were calculated using fixed points on the preoperative abdominal coronal CT scan. Port placements were marked on the CT scan. The fixed points used to measure the manipulation angles were from the most lateral part of the caecum, hepatic flexure, splenic flexure, the descending colon/sigmoid colon junction and the sigmoid colon/rectum junction. Results: For right hemicolectomy and high anterior resection surgery, a port spacing of 8 cm compared with 6 cm resulted in greater manipulation angles. With 6‐cm port spacing, wider manipulation angles were not achieved with vertical port alignment compared with oblique alignment except for dissection at the splenic flexure. Conclusions: The greatest manipulation angles were achieved with the oblique 8‐cm port spacing, which should be used in most cases.